2022
DOI: 10.1039/d2ra00032f
|View full text |Cite
|
Sign up to set email alerts
|

Using a two-step method of surface mechanical attrition treatment and calcium ion implantation to promote the osteogenic activity of mesenchymal stem cells as well as biomineralization on a β-titanium surface

Abstract: Combination of the SMAT technique and Ca-ion implantation produced a β-titanium alloy with a bioactive surface layer, which was proved to effectively promote the osteogenic activity of MSCs and Ca–P mineral deposition in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…143) A limited surface hardening was observed for an orthopedic TiNbSn alloys after SMAT but SMAT enhanced the cell proliferation rate and, more importantly, the osteogenic differentiation of stem cells. 107) SMAT treatment followed by calcium ion implantation has been tested on the Ti25Nb 3Mo2Sn3Zr ¢-Ti alloy by Huang et al 144) The SMATed samples showed improved hydrophilicity compared to the untreated samples. Subsequent Ca ion implantation further improved wettability.…”
Section: Titanium Alloysmentioning
confidence: 99%
“…143) A limited surface hardening was observed for an orthopedic TiNbSn alloys after SMAT but SMAT enhanced the cell proliferation rate and, more importantly, the osteogenic differentiation of stem cells. 107) SMAT treatment followed by calcium ion implantation has been tested on the Ti25Nb 3Mo2Sn3Zr ¢-Ti alloy by Huang et al 144) The SMATed samples showed improved hydrophilicity compared to the untreated samples. Subsequent Ca ion implantation further improved wettability.…”
Section: Titanium Alloysmentioning
confidence: 99%
“…Therefore, the biomineralization of HA onto surfaces of synthetic polymer scaffolds can form a bioactive surface with higher wettability and better osteoinductivity, which provides a more favorable microenvironment for osteoblast adhesion, proliferation, and differentiation [ 20 , 21 ]. Currently, soaking in a simulated body fluid (SBF) that contains similar ion levels to those of human body fluid is one of the most common biomineralization approaches and has the advantages of being a simple procedure and having high efficiency [ 22 ]. However, biomineralized coating fabricated by immersion in simulated body fluid is uneven and unstable.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the two-step method is extensively used for producing nanostructured materials like Al2O3 nanoparticles. [10]. The dry powder that is produced after using the physical and chemical processes is then dissolved in the base fluid (water).…”
Section: Introductionmentioning
confidence: 99%